Screening for colorectal cancer using the faecal occult blood test, Hemoccult - Towler, BP; Irwig, L; Glasziou, P; Weller, D; Kewenter, J (Wiley, 1998)
Background: Colorectal cancer is a leading cause of illness and death in the Western world. In Australia, the United Kingdom and the United States, it is the second commonest cancer for women after breast cancer (age‐standardised incidence 22‐33 per 100,000), and men after prostate or lung cancer (age‐standardised incidence 31‐47 per 100,000) (Jeffs et al, 1996; Parkin et al, 1992). Just under half of all persons affected will die from their disease (Jeffs et al, 1996; Parkin et al, 1992) The human and financial costs of this disease have prompted considerable research efforts to evaluate the ability of screening tests to detect the cancer at an early curable stage. Tests which have been considered for screening include faecal occult blood tests, sigmoidoscopy and colonoscopy. Objectives: To determine whether screening for colorectal cancer using the faecal occult blood test, Hemoccult reduces colorectal cancer mortality and to consider the benefits and harms of screening. Search methods: Published and unpublished data for this review were identified by: retrieving studies included in a systematic review conducted by some of the authors in 1995, searches of MEDLINE, Current Contents and the Cochrane Controlled Trials Register, writing to trial lists. Selection criteria: All controlled trials of screening for colorectal cancer using Hemoccult were eligible for inclusion in the review. Data collection and analysis: Data from the trials were independently extracted by two authors. Data analysis was performed using the group subjects were randomised to ('intention to screen'), whether or not they were ever screened. To estimate the effect of Hemoccult screening on colorectal cancer mortality, we calculated relative risks and risk differences for each trial, and then overall, using fixed and random effects models and tested for heterogeneity of effects. We calculated summary measures of effect including all trials and also for just the randomised controlled trials. We also calculated a summary measure of effect, adjusted for attendance at screening in each trial (not shown in Meta‐view).